Dolly, Cloning, and the Public Misunderstanding of Science: A Challenge for Us All - Klotzko, Arlene Judith (Cambridge quarterly of healthcare ethics, 1998)
It has become a commonplace to observe that the people of the world will soon be divided into two classes—the technologically literate and everyone else. While such a situation certainly has unfortunate economic effects—for everyone else—how much worse it would be if we made a slight alteration in our description. How much worse it would be if the vast majority of people were possessed of too little information to allow them to make informed decisions about their own lives, health, and genetic inheritance. Unfortunately, this is the reality. And as scientific advances rocket far ahead of both our bemused journalistic establishment and our limping regulatory apparatus, the reality becomes ever more pernicious.